Occult clavicle osteomyelitis caused by Cutibacterium acnes (C. acnes) after coracoclavicular ligament reconstruction: A case report and review of the literature. (May 2022) - Washburn, Frederic; Tran, Britni; Golden, Thomas
Abstract: Introduction: Clavicle osteomyelitis is a rare, but serious complication following operative repair of acromioclavicular (AC) joint separations. Cutibacterium Acnes ( C. acnes ) is rarely a causative pathogen in clavicle osteomyelitis and diagnosis can be challenging due to the indolent nature of this organism. Case presentation: A 45–50 year old female with a chronic AC joint separation underwent an open coracoclavicular reconstruction using semitendinosus allograft and FiberTape (Arthrex, Naples, FL). At the six month follow up, the patient complained of mild persistent pain. Imaging demonstrated widening of the medial suture tunnel with distal clavicle osteolysis, which was concerning for osteomyelitis. This was successfully treated with implant removal revision surgery and additional intravenous antibiotics. Cultures of the graft material were positive for C. acnes. The patient continued to have osteolysis of the distal left clavicle for a period of time despite resolution of osteomyelitis. Discussion: C. acnes osteomyelitis of the clavicle is difficult to diagnose because of its vague associated symptoms when implicated in infections. There are no known obvious predisposing factors for C. acnes clavicle osteomyelitis. Literature suggests management should include aggressive irrigation and debridement, removal of any hardware, and extended intravenous antibiotic administration. Conclusion: C. acnes clavicular osteomyelitis is uncommon, thus established treatment guidelines have not yet been formed. Revision surgery to remove graft material, irrigate, and debride in addition to antibiotic treatment was successful for our patient. Additional pathologic manifestations of C. acnes infections could include continued clavicular erosion post-clearance of infection, although further investigation is necessary. Highlights: C. acnes osteomyelitis after coracoclavicular ligament reconstruction is rare. Culturing and identifying indolent C. acnes infection is difficult. Symptoms are generally nonspecific with unremarkable host inflammatory responses. All suture and graft material must be removed to eradicate this infection. Patient had continued distal clavicle osteolysis despite resolution of osteomyelitis.